Experiences of Library Professionals on DSpace Installation - Nyaichyai, Lila; Luitel, Goma; Maharjan, Ram Krishna (Nepal Journal of Multidisciplinary Research, 2021)
DSpace, a free and open-source software (FOSS) provides the digital platform for building collections of an institution. Due to the lack of the skills to install and configure DSpace, librarians are incapable to conduct it even after the awareness about it. Identifying challenges about DSpace installation is vital to increase its use by librarians. Hence, it aims to explore the understanding of DSpace installation among librarians and to identify aspects of their experiences and feelings while installing DSpace. Librarians' experiences and feelings are important for accepting the software. Librarians were interviewed during the training program conducted on digital library technology from December 2020 to January 2021. Two groups were distinguishing from each other: one is with a library science background and another is with computer science and engineering background. The second group aswas self-sustained to install DSpace, once they got the guidelines for installation. Their views were reflected with the code terms status, exploration, feeling, activities, preferences, and inadequacy. Through their experiences, the aspects of challenges are the less experience of using the command line in computer use, the unavailability of teaching courses on Linux operating system in Library and Information Science (LIS) education, and the lack of self-exploration habits. Practice to Linux commands, incorporate the Linux in the Library Science course, self-exploration, and consistent effort will help librarians in installing DSpace by themselves. Finally, librarians should internalize their goal to act as the administrator for the DSpace, not only as of the operator.